2021
DOI: 10.1002/erv.2821
|View full text |Cite
|
Sign up to set email alerts
|

Optimising care pathways for adult anorexia nervosa. What is the evidence to guide the provision of high‐quality, cost‐effective services?

Abstract: The aim of this paper is to consider how changes in service planning and delivery might improve the care pathways for adult anorexia nervosa. Although anorexia nervosa has a long history in Europe, its framing as a mental disorder is quite recent. The changing forms and increasing epidemiology of eating disorders has led to the expansion of specialised services. Although some services provide care over the entire clinical course, more often services are divided into those that care for children and adolescents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 62 publications
1
41
0
Order By: Relevance
“…The transition between inpatient and outpatient services has long been considered a possible contributing cause of frequent RAs with estimates of a lack of a link to outpatient care after an acute hospitalization ranging from 22 to 90% (40). In this vein, interventions that bridge the transition home, thus, increasing community support, have been recently authoritatively advocated for AN (41). On the other hand, it should also be noted that individualized discharge plans could have helped avoid even more rapid patterns of RAs; in fact, different from earlier studies on general psychiatry (42), the first month since hospital discharge was not a critical period for RA.…”
Section: Discussionmentioning
confidence: 99%
“…The transition between inpatient and outpatient services has long been considered a possible contributing cause of frequent RAs with estimates of a lack of a link to outpatient care after an acute hospitalization ranging from 22 to 90% (40). In this vein, interventions that bridge the transition home, thus, increasing community support, have been recently authoritatively advocated for AN (41). On the other hand, it should also be noted that individualized discharge plans could have helped avoid even more rapid patterns of RAs; in fact, different from earlier studies on general psychiatry (42), the first month since hospital discharge was not a critical period for RA.…”
Section: Discussionmentioning
confidence: 99%
“…Of concern, although in line with the literature (25)(26)(27), is that more that the half of the patients had remained underweight or returned to underweight at follow-up. These troubling findings underline the need of new therapeutic strategies to better treat severely ill patients and prevent relapse, and intensify research in this field (28).…”
Section: Discussionmentioning
confidence: 99%
“…Especially female adolescents between 15 and 19 years are affected by AN with a postulated decrease in the age of onset [7,[15][16][17][18]. Recent reviews reported a better prognosis in children and adolescents compared to patients with first-onset AN in adulthood, which emphasizes the need for early recognition, diagnosis and treatment to prevent relapse and a chronic, protracted, or enduring course of this disorder [19][20][21][22][23][24]. The complex phenomenology of this illness and its long enduring course of over 20 years in more than half of those affected, requires specially adapted treatment concepts to increase remission and recovery rates [1,3,5,24].…”
Section: Introductionmentioning
confidence: 99%
“…The intensity of the treatment setting should be adapted to the severity of the disorder, taking into account comorbidities and medical complications. Outpatient psychological/psychotherapeutic treatment involving family members (e.g., family-based treatment, parent-focused treatment, systemic family therapy, enhanced cognitive-behavioral therapy, focal psychodynamic therapy) should be the first step, eventually followed by day clinic and inpatient treatment [ 1 , 3 , 19 , 25 , 26 ]. The current recommendations for consideration of inpatient treatment include a body-mass-index (BMI) below the 3rd percentile, rapid weight loss, low energy intake, refusal to drink, medical complications, severe psychiatric comorbidity, dysfunctional family interactions, and insufficient response to outpatient treatment [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%